2005
DOI: 10.1007/s10562-005-5865-3
|View full text |Cite
|
Sign up to set email alerts
|

Real time monitoring of the evolution of Ni2+ environment in faujasite upon rehydration by in situ dispersive-EXAFS

Abstract: The evolution of both oxygen and framework tetrahedral shells around Ni 2+ cations in faujasite upon rehydration can be described in real time thanks to in situ dispersive-EXAFS. Such type of analysis permits precise experimental description of the coordination environment of cations in zeolite structures under different hydration conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 13 publications
0
15
0
Order By: Relevance
“…5B), which has only a single peak at about 1.6 Å , indicating a single shell of back-scattering O atoms neighboring the central Ni atom. The quantitative analysis shows that Ni is coordinated with $6 O atoms at interatomic distances of 2.05 Å in Ni(II)(aq) ( (Dooryhee et al, 1991;Groust et al, 2005). The [Ni(H 2 O) 6 ] 2+ solution is immediately generated upon dissolution of simple nickel salts in water (Xu et al, 2007).…”
Section: Exafs Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…5B), which has only a single peak at about 1.6 Å , indicating a single shell of back-scattering O atoms neighboring the central Ni atom. The quantitative analysis shows that Ni is coordinated with $6 O atoms at interatomic distances of 2.05 Å in Ni(II)(aq) ( (Dooryhee et al, 1991;Groust et al, 2005). The [Ni(H 2 O) 6 ] 2+ solution is immediately generated upon dissolution of simple nickel salts in water (Xu et al, 2007).…”
Section: Exafs Analysismentioning
confidence: 99%
“…The remaining Ni 2+ ions in a partially solvated state in the sodalite cage were readily reducible by hydrogen to yield small crystallites of metallic nickel. Groust et al (2005) used in situ dispersive-EXAFS to identify the oxygen and framework tetrahedral shells around Ni 2+ in faujasite upon rehydration and found that the Ni 2+ in fully hydrated Ni 2.6 NaX were present in an [Ni(H 2 O) 6 ] 2+ octahedral environment at Ni-O distance of 2.06 Å . In contrast, the Ni-O distance of 2.11 Å in dehydrated Ni 2.6 NaX is close to a value previously proposed considering that faujasite is able to accommodate effectively Ni 2+ at site SI (center of the hexagonal prism) with six framework O atoms at a bond distance of 2.10 Å (Dooryhee et al, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…180°C, while no weight loss is observed. A probable hypothesis would arise in a rearrangement of the nickel polyhedron, as observed elsewhere 58,59 and as discussed below (see Structural Evolution of the Lamellar Phases upon Dehydration).…”
Section: ■ Introductionmentioning
confidence: 77%
“…[18][19][20][21][22][23] In addition, the propensity of cations to move from one particular site to another (possibly in a distinct cage) upon addition of molecules, for instance adsorbed water or a reactant, has been largely demonstrated. [24][25][26] Nevertheless, due to the entailed computational cost of DFT, accurate theoretical descriptions are currently limited to clusters containing only up to a few 10-100 atoms. For zeolites, in which unit cells usually contain more than 100 TO 2 tetrahedra (i.e.…”
Section: ) Introductionmentioning
confidence: 99%